Penerapan Algoritma Backtracking Dengan Bounding Function Dan Depth First Search Pada Permainan Boggle - Nurhasanah, Nurhasanah; Saptoni, Uden (Universitas Gajah Putih, 2023)
Using the backtracking algorithm with a bounding function and Depth-First Search (DFS) in the game of Boggle enables efficient search through the solution space to find valid solutions. In the backtracking algorithm, the steps taken involve decision-making and restoring the previous state if the problem does not lead to a valid solution. The bounding function is used to limit unnecessary search space, significantly improving efficiency.The Depth-First Search (DFS) method is employed to perform a deep search into the solution space. DFS visits nodes in a sequential manner, delving deeper into each node before moving on to its children nodes. In the context of the game, this means attempting all possible steps before transitioning to the next step.